A comparative study of maternity leave in Iranian and Swedish law - Mehdi Hadavand; Fatemeh Nowrouzi (پژوهشهای حقوقی, 2023)
Maternity leave is important for the health of mothers and their children, as well as the participation of working mothers in the labor market and their economic situation, and the International Labor Organization in the conventions and recommendations on the importance and necessity of support Motherhood emphasizes working women . In the reports of this organization, Scandinavian countries such as Sweden are evaluated at a high level in many criteria such as equality, welfare, etc. Sweden has policies in place to increase the participation of working mothers in the labor market, and with the passage of the Parental Leave Act, it seeks to achieve this goal as well as increase gender equality; This type of leave is currently highly regarded and adapted worldwide. The findings show that in addition to legal protections for women during this period, parental leave implemented in Sweden is well in line with the work-family policy emphasized by the International Labor Organization. In the Iranian legal system, despite legal protections during pregnancy, childbirth and breastfeeding, which also exist in Sweden, paternal' leave is short, and this has a significant impact on women's participation in the labor market. The present article seeks to examine the maternity leave in the two legal systems of Iran and Sweden with a descriptive-analytical method and the importance of legal protections for women in this important period and its impact on their participation in the labor market. And also examine gender equality.